REFLEKSI ATAS PERLINDUNGAN HAK ASASI MANUSIA DI PROVINSI PAPUA - Roni Sulistyanto Luhukay (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2021)
ABSTRACT The problem of handling Human Rights against Indigenous Papuans can be seen by the existence of violence and violations of human rights in all aspects of the lives of Indigenous Papuans in a systematic, sustainable and unstoppable manner. politics where the more indigenous Papuans are involved in politics, the faster the resolution of human rights in Papua because of the large number of representatives who are fighting for the liberation of the Papuan people, meaning that in this problem the Political Rights of Papuan Indigenous People in the National Legislative Body need to get support and protection of human rights on the ground Papua has not been able to run properly due to various indicators that have not been able to run properly. These indicators include the absence of a representative of the National Human Rights Commission; human rights courts, and truth and reconciliation commissions as well as the absence of special fund allocations in the field of human rights in the context of implementing the Special Autonomy Law in Papua, not only that this regulation does not work properly so that it has the potential to be increasingly unstoppable for human rights violations, in its implementation Human rights protection cannot run properly considering that in this regulation there is still uncertainty regarding the meaning, relationship, and purpose of the norms contained in the Papua Special Autonomy Law as well as unclear and limited special powers intended in the Autonomy Law Papua Special. This study emphasizes normative legal research and is balanced by looking at the condition of human rights violations in Papua by multiplying several literacies.